Genetic characterization of an H3N2 canine influenza virus strain in China in 2023—acquisition of novel human-like amino acid substitutions - Li, Sihan; Chu, Liangyu; Zhang, Yancheng; Yu, Yaxuan; Wang, Guoqing (Frontiers in Veterinary Science, 2025)
Around 2005, influenza A virus (IAV) once again crossed species barriers and established a stable lineage within canine populations. Currently, avian-origin H3N2 canine influenza virus (CIV) is the only strain of influenza that is stably circulating in canine populations. Initially, this virus was detected exclusively in Asian countries, such as China and South Korea. However, in 2015, it was isolated from dogs in the United States, where it subsequently caused a large-scale outbreak. Since its initial isolation, the H3N2 CIV has demonstrated the ability to infect mammals, including cats. Throughout its spread, the virus has continuously enhanced its adaptability to mammalian hosts, posing a potential public health threat. To monitor the prevalence of H3N2 CIV in China, we collected 131 nasal swabs from dogs and cats with respiratory symptoms between December 2023 and February 2024 in Beijing, Changchun, Shenyang, Hohhot, and Yunfu. From these samples, one influenza virus strain was successfully isolated. Through whole-genome sequencing and phylogenetic analysis, this strain was identified as avian-origin H3N2 CIV. All eight gene segments exhibited amino acid substitutions, with PB2 107 N, HA1 202I, and M1 227T positions being identical to those found in the currently circulating H3N2 human influenza virus (HuIV). Interestingly, by around 2021, the H3N2 HuIV had already completed the PB2 107 N substitution. Our study indicates that H3N2 CIV is evolving toward increased adaptability to mammalian hosts, highlighting the necessity for strengthened monitoring and risk assessment.